2020
DOI: 10.1111/azo.12367
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of the tongue surface and lingual glands of the Sulawesi bear cuscus, Ailurops ursinus (Marsupialia: Phalangeridae)—A light and scanning electron microscopic study

Abstract: This study aimed to evaluate the microstructure of the surface of the tongue and lingual glands of the vulnerable native Sulawesi bear Ailurops ursinus. The study was carried out on five tongues collected from four adult animals and one young animal. There was variation in the shape of the filiform papillae. Few conical papillae were observed on the caudo‐lateral surface of the tongue. The gustatory papillae included fungiform papillae on the entire lingual surface and three vallate papillae, with the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The tongue morphology, in its macroscopic structure (tongue papillae types, shape, function, and distribution) in vertebrates, varies to fit their diets (i.e., whether they are carnivores, omnivores, or herbivores) as well as their environments and habitats, which may have played a partial role in the evolution of the tongue's structure (Iwasaki et al 2019). Such an adaptation based on the diet, environment, or habitat has been described in various studies, especially in mammals, such as goats (Mahdy et al 2021), pumas (Erdogan et al 2018), sugar gliders (Damia et al 2021), and several other carnivores, including polar bears, marsupials, and bats (Emura et al 2017;Gozdziewska-Harlajczuk et al 2020;Gunawan et al 2020). In a study, the tongue morphology revealed a relationship between changes in the habitat and changes in the appearance of the tongue; the transition from a freshwater (moist or wet) environment to a terrestrial (dry) environment resulted in the keratinisation of the lingual epithelium (Iwasaki 2002).…”
Section: Discussionmentioning
confidence: 98%
“…The tongue morphology, in its macroscopic structure (tongue papillae types, shape, function, and distribution) in vertebrates, varies to fit their diets (i.e., whether they are carnivores, omnivores, or herbivores) as well as their environments and habitats, which may have played a partial role in the evolution of the tongue's structure (Iwasaki et al 2019). Such an adaptation based on the diet, environment, or habitat has been described in various studies, especially in mammals, such as goats (Mahdy et al 2021), pumas (Erdogan et al 2018), sugar gliders (Damia et al 2021), and several other carnivores, including polar bears, marsupials, and bats (Emura et al 2017;Gozdziewska-Harlajczuk et al 2020;Gunawan et al 2020). In a study, the tongue morphology revealed a relationship between changes in the habitat and changes in the appearance of the tongue; the transition from a freshwater (moist or wet) environment to a terrestrial (dry) environment resulted in the keratinisation of the lingual epithelium (Iwasaki 2002).…”
Section: Discussionmentioning
confidence: 98%
“…The lingual torus appears to be a characteristic structure that has developed primarily in herbivorous animals (Zheng & Kobayashi, 2006), although it is absent in equids and some folivores belonging to the Marsupialia or Pilosa (Abd‐Elnaeim et al, 2002; Benetti et al, 2009; Emura, 2018; Goździewska‐Harłajczuk et al, 2022). Indeed, the lingual torus has been described in many ruminant or tylopod artiodactyls, regardless of whether they were browsers, intermediates or grazers.…”
Section: Discussionmentioning
confidence: 99%
“…The proper manipulation of foodstuff in the stomach and intestine of a particular species allows better absorption of nutrients. However, food preprocessing in the buccal cavity plays a crucial role in this process (Goździewska‐Harłajczuk et al, 2022). The desert hedgehog mainly consumes insects and small invertebrates (Massoud, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The macroscopic observations showed that there was no lingual prominence detected on the tongue dorsum. The emergence of this part in the tongue dorsum was detected in several species, including Sulawesi bear (Goździewska‐Harłajczuk et al, 2022), koala (Kobayashi et al, 2003), Egyptian water buffalo (Farrag et al, 2022), lowland tapir (Goździewska‐Harłajczuk et al, 2020), barking deer (Adnyane et al, 2010), Wistar rat (Huțanu et al, 2022), and Nile grass rat (Massoud & Abumandour, 2019). It appears that the existence of lingual prominence is closely linked to herbivorous feeding habits to grind grass and hard food materials against the hard palate and crush teeth (Haggag et al, 2020).…”
Section: Discussionmentioning
confidence: 99%